2018
DOI: 10.1111/dmcn.14015
|View full text |Cite
|
Sign up to set email alerts
|

First‐ever convulsive seizures in children presenting to the emergency department: risk factors for seizure recurrence and diagnosis of epilepsy

Abstract: Seizures were 'unprovoked' in 19.4% and 'provoked' in 80.6% of children presenting to the emergency department. At 4-year follow-up, 37.9% relapsed, and 13.6% received a diagnosis of epilepsy. 'Unprovoked' first seizure, family history of febrile seizures, and pre-existing neurological conditions were associated with recurrence. 'Unprovoked' first seizure, age younger than 6 years, and pre-existing neurological conditions were associated with epilepsy diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 44 publications
(120 reference statements)
2
22
1
Order By: Relevance
“…8 Children who have had one epileptic seizure have a high risk of recurrent epileptic seizures and epilepsy. 9,10 Despite distinctive pathophysiological features, distinguishing syncope from epileptic seizures may be difficult because non-epileptic disorders can have a similar history or clinical presentation to epilepsy. 11e16 The head-up tilt test (HUTT) may help to distinguish epilepsy from simple or convulsive syncope in a subset of patients.…”
Section: Introductionmentioning
confidence: 99%
“…8 Children who have had one epileptic seizure have a high risk of recurrent epileptic seizures and epilepsy. 9,10 Despite distinctive pathophysiological features, distinguishing syncope from epileptic seizures may be difficult because non-epileptic disorders can have a similar history or clinical presentation to epilepsy. 11e16 The head-up tilt test (HUTT) may help to distinguish epilepsy from simple or convulsive syncope in a subset of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Population-based studies indicate that acute symptomatic seizures represent 40-50% of all cases of seizures. 12,17 Sartori et al 18 reported that 32.5% of patients with acute symptomatic seizures experienced seizure recurrence at 4-year follow-up. In our study, 83 (60%) patients presented with acute symptomatic seizures.…”
Section: Discussionmentioning
confidence: 99%
“…Studies has demonstrated that up to 25 to 50% of children with SFS have family history of febrile seizures, suggesting a strong genetic component in febrile seizures. 9 A clear genetic etiology has been identified in some genetic epilepsy syndromes associated with occurrence of febrile seizures. One of the first syndromes identified is genetic epilepsy with febrile seizures plus (GEFSþ).…”
Section: Epidemiology and Pathophysiologymentioning
confidence: 99%
“…The most important predictive risk factors for the development of epilepsy are developmental delay, abnormal neurological exam prior to the febrile seizure, history of complex febrile seizures or febrile status epilepticus, and a first degree relative with epilepsy. 5,9,34 The exact mechanism for development of epilepsy is complex and not fully elucidated. These risk factors may suggest a preexisting predisposition to develop epilepsy.…”
Section: Risk Factors For Recurrence Of Febrile Seizuresmentioning
confidence: 99%